Convex functions, partial orderings, and statistical applications - Pečarić, Josip E. (Mathematics in science and engineering, 1992)
This research-level book presents up-to-date information concerning recent developments in convex functions and partial ordering and some applications in mathematics, statistics, and reliability theory. The book will serve researchers in mathematical and statistical theory and theoretical and applied reliabilists.